Evidence for Causal Relations between Executive Functions and Alphabetic Skills Based on Longitudinal Data. Issue 1 (14th November 2013) - Kegel, Cornelia A. T.; Bus, Adriana G.; Mulder, Hanna; Cragg, Lucy
<x xml:space="preserve">Abstract</x> Children showing poor executive functioning may not fully benefit from learning experiences at home and school and may lag behind in literacy skills. This hypothesis was tested in a sample of 276 kindergarten children. Executive functions and literacy skills were tested at about 61 months and again a year later. In line with earlier studies, correlations between both skills were significant at age 5 years, but the predictive value of executive functions on alphabetic skills weakened or disappeared 1 year later. Assuming that executive functions are in development at this age and change has to be taken into account, we applied fixed effects analyses (FEAs) to repeated measures of alphabetic skills and executive functions. FEAs demonstrated that changes in children's alphabetic skills concur with changes in executive functions, thus strengthening inferences about a causal relationship. Executive functions are unstable in the early stages of cognitive development and one‐time measures cannot predict their impact on reading 1 year later. Consequences of this new insight are discussed. Copyright © 2013 John Wiley & Sons, Ltd.